Cover Image. Issue 2 (12th March 2018) - Molyneux, J.; Gordon, J. S.; Schoenberg, F. P.
Abstract : The cover image, by J. Molyneux et al., is based on the Research Article Assessing the predictive accuracy of earthquake strike angle estimates using nonparametric Hawkes processes, DOI:10.1002/env.2491 .